Pengaruh Penerapan Program Adiwiyata terhadap Kesadaran dan Peduli Lingkungan Siswa Kelas VII UPT SMPN 1 Sanankulon - M. Rivan Eko Mahendra; Nur Isroatul Khusna (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study was motivated by the decline in the cleanliness quality of the school environment due to students’ low awareness and concern for environmental preservation. The Adiwiyata Program is expected to cultivate a culture of environmental care in schools, although its implementation has not been optimal. This study aims to analyze the influence of the Adiwiyata Program implementation on the environmental awareness and concern of seventh-grade students at UPT SMPN 1 Sanankulon, as well as the relationship between awareness and concern. The research used a quantitative approach with a causal-comparative method. A total of 26 students were selected as the sample using the Slovin formula. Data collection was conducted using questionnaires, and data analysis involved simple linear regression and correlation coefficient tests. The results showed that the implementation of the Adiwiyata Program had a significant influence on environmental awareness (67.1%) and environmental concern (82.4%). Furthermore, there was a strong and positive relationship between environmental awareness and concern, indicated by a Pearson correlation value of 0.762. These findings imply the importance of optimizing the Adiwiyata Program to enhance students' environmental awareness and concern within the school environment.